RUSSIAN TRANSLATION OF MILLER’S ANESTHESIA: EXPERIENCE, FINDINGS AND ERRORS - Yu. S. Аleksandrovich; K. S. Baudis; A. I. Gritsan; D. B. Ivanov; I. B. Zabolotskikh; A. P. Zil’ber; M. Yu. Kirov; K. M. Lebedinskiy; V. V. Likhvantsev; V. V. Subbotin; A. V. Schyogolev (Вестник анестезиологии и реаниматологии)
Translators and editors of the first Russian edition of Miller’s Anesthesia analyze one of the biggest publication projects for anesthesiology and intesive care in RF, implemented by 109 specialists from 11 countries all over the world without involvement of professional translators. In order to support future similar translations special attention is paid to organizational details and errors.